Modern and Postmodern Crises of Symbolic Structures : Essays in Philosophical Anthropology - Šajda, Peter, (Value Inquiry Book Series ;, 2021)
In debates about philosophical anthropology human beings have been defined in different ways. In Modern and Postmodern Crises of Symbolic Structures , the contributors view the human being primarily as animal symbolicum. They examine how the human being creates, interprets and changes symbolic structures, as well as how he is affected and impacted by them. The focus lies on the context of modernity and postmodernity, which is characterized by a number of interrelated crises of symbolic structures. These crises have affected the realms of science, religion, art, politics and education, and thus provoked crucial changes in the human being's relations to himself, others and reality. The crises are not viewed merely as manifestations of dysfunctions, but rather as complex processes of transformation that also provide new opportunities.